Potency of probiotic on broiler growth performance and economics analysis - ANDRIANI, ANITA DWI; LOKAPIRNASARI, WIDYA PARAMITA; KARIMAH, BALQIS; HIDANAH, SRI; AL-ARIF, M ANAM (The Indian Journal of Animal Sciences, 2021)
The study was undertaken to know the economic analysis in broilers fed probiotic containing Lactobacillus casei and Lactobacillus rhamnosus supplementation in lieu of antibiotic growth promoters (AGP) to feed conversion ratio (FCR) and body weight (BW). The treatments were T0: control, T1: 0.01 g AGP/kg feed, T2: 0.05 g/ kg feed, T3: 0.1 g/ kg feed, T4: 0.025 g probiotic/litre drinking water; T5: 0.05 g probiotic/liter drinking water. Data analysis was carried out using the Analysis of Variance (ANOVA) method, business analysis was held out by XLSTAT then analyzing descriptively. The results indicated that there was a significant difference among the treatments. Probiotic administration of T2, T3, T4 and T5 could increase broiler's body weight and improve feed conversion ratio. The higher production performance and most profitable economic analysis was obtained with the addition of 0.025 g probiotic/litre (T4), which had the best results in a Break Even Point and Return Cost Ratio. It could be concluded that supplementation of 0.025 g probiotic/litre drinking water indicates the improve growth performance and profits in broiler.